2020
DOI: 10.1021/acsabm.0c01098
|View full text |Cite
|
Sign up to set email alerts
|

Immunoassay of Tumor Markers Based on Graphene Surface-Enhanced Raman Spectroscopy

Abstract: With a unique chemical enhancement capability, graphene oxide is exceptionally suitable to serve as an alternative surface-enhanced Raman scattering (SERS) substrate, which is usually defined as GERS. However, such a GERS matrix with both promising uniformity and molecule enrichment ability has not been applied in the quantitative detection of tumor markers. Herein, an ultrasensitive and specific immunoassay of carcinoembryonic antigens mediated by the GERS matrix was demonstrated. With the assistance of Au NR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…RhB on GO and RGO exhibits a higher enhancement of Raman signals as compared to other dye molecules. The Raman scattering cross-section of RhB is larger as compared to the other dyes; it is another result of RhB exhibiting a higher SERS effect than other dyes . The sensitivity of both GO and RGO to detect RhB molecules is very high, which can be traced down to 10 –8 M. Therefore, the RhB dye is studied using the gas plasma-treated GO and RGO samples to improve its SERS sensitivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RhB on GO and RGO exhibits a higher enhancement of Raman signals as compared to other dye molecules. The Raman scattering cross-section of RhB is larger as compared to the other dyes; it is another result of RhB exhibiting a higher SERS effect than other dyes . The sensitivity of both GO and RGO to detect RhB molecules is very high, which can be traced down to 10 –8 M. Therefore, the RhB dye is studied using the gas plasma-treated GO and RGO samples to improve its SERS sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Ling et al first observed the effect of graphene on Raman signals in which many unknown peaks emerged when the graphene substrate was treated with an organic solvent as compared to that of the SiO 2 /Si substrate. Several other studies have reported the sensing efficiency of the graphene-based sheet through enhancement of the Raman signal. Jin-Ha Choi et al demonstrated the reliability of graphene-hybrid (gold array) as the SERS sensing substrate developed by laser interference lithography and the electrochemical deposition method for detecting 10 –4 to 10 –9 M concentration of dopamine. A single molecule (10 –15 M) of rhodamine 6G was detected by using a three-dimensional GO quantum sensor with an enhancement factor (EF) of 10 14 times .…”
Section: Introductionmentioning
confidence: 99%
“…146 Recently, Jiang and co-workers developed a GO-based ultrasensitive SERS substrate for CEA detection. 147 By utilizing gold nanorods as immunoprobes, this GO enhanced SERS platform provided a dynamic linear range from 10 pg mL −1 to 1 μg mL −1 with an LOD of 3.01 pg mL −1 for CEA detection. 147…”
Section: Nanostructured Substrate Surfaces For Signal Enhancementmentioning
confidence: 99%
“…7 Traditional SERS substrates commonly have gold or silver nanostructures on rigid flat-based materials such as silicon wafer and glass slides. 8,9 But, this kind of SERS substrate is difficult to integrate with other devices and lacks flexibility, which severely limits its further applications. With the rapid development of nanotechnology, more functional materials, such as capillary, 10 filter paper, 11 and microfiber, 12,13 have received enormous attention from researchers and have been used in the fabrication of SERS substrates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Surface-enhanced Raman spectroscopy (SERS) is one of the sensitive techniques with the possibility of single-molecule detection arising from fingerprint vibration spectrum. ,, It is well known that the enhancement of Raman scattering is driven by chemical and/or electromagnetic interactions, which are mainly manipulated by the metal nanostructures of the SERS substrates . Traditional SERS substrates commonly have gold or silver nanostructures on rigid flat-based materials such as silicon wafer and glass slides. , But, this kind of SERS substrate is difficult to integrate with other devices and lacks flexibility, which severely limits its further applications. With the rapid development of nanotechnology, more functional materials, such as capillary, filter paper, and microfiber, , have received enormous attention from researchers and have been used in the fabrication of SERS substrates.…”
Section: Introductionmentioning
confidence: 99%